Pengaruh Ukuran Perusahaan, Profitabilitas, dan Intellectual Capital Terhadap Harga Saham Perusahaan: Studi Empiris Perusahaan Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2021 – 2023 - Naufal Maulana Waluyo; Muslimin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Public interest in stock market investments increased significantly between 2020 and 2023, with the food and beverage industry becoming as one of the most alluring sectors during this time. Despite its popularity, stock prices in this sector have consistently declined each year due to various influencing factors. Investigating company size, profitability, and intellectual capital effects on stock prices of the food and beverage firms listed on the Indonesia Stock Exchange (IDX) since 2021 until 2023 is being the point of this research. Using a quantitative approach methodology, this study focuses on 46 companies in the sector that meet certain criteria. In addition to standard hypothesis and assumption testing, the finding data was processed using multiple linear regression analysis. The findings indicate that profitability and intellectual capital have a major impact on Price to Book Value (PBV). However, there is no apparent correlation between PBV and firm size. Nonetheless, it is found that the PBV of food and beverage firms listed on the Indonesia Stock Exchange (IDX) since 2021 until 2023 is considerably and simultaneously affected by firm size, profitability, also intellectual capital when considered collectively.